Editorial of Special Issue "Current Trends in Chemistry Towards Biology" - Kos, Jiri; Jampilek, Josef (International journal of molecular sciences, 2024)
One of the definitions of chemical biology is that it is a scientific discipline spanning the fields of chemistry, biology, and physics; it primarily involves the application of chemical techniques, tools, analyses, and often compounds (also known as chemical probes), which are produced through synthetic chemistry, in order to study and manipulate biological systems [...].
Keywords: biologie; Humans; Biology; chemie; lidé; Chemistry